2023
DOI: 10.3892/ijo.2023.5483
|View full text |Cite
|
Sign up to set email alerts
|

FUT2 promotes the tumorigenicity and metastasis of colorectal cancer cells via the Wnt/β‑catenin pathway

Abstract: The incidence of colorectal cancer (CRC), a leading cause of cancer-related mortality, has increased globally. Fucosyltransferase 2 (FUT2), catalyzing the α1, 2-linked fucose in mammals, has been reported to be overexpressed in several malignant cancers, including CRC. However, the effects of FUT2 on CRC remain largely unknown. Herein, it was determined that the FUT2 expression levels in CRC tissues were higher than those in adjacent non-tumor tissues, whereas no association with tumor stage was revealed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…We previously reported that FUT2 is upregulated in clinical CRC tissue, compared to matched normal tissues from the same patients [18]. Here, the data from TCGA and GTEx databases revealed that FUT2 gene expression is elevated in CRC tumors compared to normal colorectal tissues (Fig.…”
Section: Fut2 Is Upregulated In Crc and Correlated With Clinical Outc...supporting
confidence: 51%
See 3 more Smart Citations
“…We previously reported that FUT2 is upregulated in clinical CRC tissue, compared to matched normal tissues from the same patients [18]. Here, the data from TCGA and GTEx databases revealed that FUT2 gene expression is elevated in CRC tumors compared to normal colorectal tissues (Fig.…”
Section: Fut2 Is Upregulated In Crc and Correlated With Clinical Outc...supporting
confidence: 51%
“…Xenograft nude mouse model was performed as previously described [18]. Tumors were stored in liquid nitrogen for further experiments.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, the tumor-promoting FUT2 and FUT8 expression was highly expressed in tumor colon cE02, cE03, and cE06 epithelial subsets in aging colon tumor. Increased FUT2 and FUT8 expression has been linked to cancer ( 45 , 46 ). Additionally, older patients with a tumor exhibited elevated FUT2, FUT3, and FUT8 coexpression with tumor-promoting IL6ST, IL22RA1, TGFB1, and TGFBR1 genes compared with young tumor.…”
Section: Discussionmentioning
confidence: 99%